Child malnutrition, a view from various factors - Alvarez Ortega, Luzvelia G. (2019)
The research objective was to determine the related factors to the prevalence of malnutrition in children under 3 years old in the province of Huánuco. It was an observational, prospective, cross-sectional, analytical and correlational study; with a random sample of 234 children, to whom were applied valuation sheets and to their mothers a questionnaire of factors; previously validated and reliable, according to ethical considerations. Se realizó un análisis descriptivo e inferencial mediante la prueba Chi cuadrada de Pearson, y la prueba multinomial, para un p ≤ 0.05, apoyados en el SPSS V22. A meaningful relationship was found between different factors: mother's unawareness of number of rations that the child should consume from the sixth month, economic inaccessibility for the food supply, rotation of traditional agricultural crops by inefficient commercials, low weight of born (p <0.05), among others. In the multivariate analysis: the rotation of traditional crops by inefficient commercials, the child with low birth weight and the poor quality of maternal and child services, increased the probability of having malnutrition. To sum up, the undernutrition in children under 3 years old is related to economic, environmental, cultural, biological and institutional factors.